2015
DOI: 10.1037/fam0000108
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic coping mediates the association of sanctification with marital satisfaction and well-being.

Abstract: Some studies suggest that the sanctification of marriage, or considering marriage sacred, is related to positive marital outcomes (e.g., marital satisfaction, conflict resolution). However, the mechanisms explaining this association have not been sufficiently investigated. In the current study, we analyzed supportive dyadic coping as a potential mediator of the relation between marriage sanctity and marital satisfaction, as well as between marriage sanctity and well-being. Self-reported data were collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 34 publications
4
34
0
1
Order By: Relevance
“…Greater sanctity of marriage also buffers married first-time parents from marital distress typically associated with viewing oneself as under or over-benefitting in the union (DeMaris et al 2010). Furthermore, greater sanctity of marriage has been repeatedly tied to greater subjective marital satisfaction, forgiveness, and sacrifice (e.g., Rusu et al 2015;Sabey et al 2014). Thus, the current study's findings echo theory and research on sanctification across multiple domains of life positing that viewing a union as sacred motivates people to invest effort to protect their bond, especially during times of stress (Mahoney 2013;Mahoney et al 2013;Pargament et al 2017).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Greater sanctity of marriage also buffers married first-time parents from marital distress typically associated with viewing oneself as under or over-benefitting in the union (DeMaris et al 2010). Furthermore, greater sanctity of marriage has been repeatedly tied to greater subjective marital satisfaction, forgiveness, and sacrifice (e.g., Rusu et al 2015;Sabey et al 2014). Thus, the current study's findings echo theory and research on sanctification across multiple domains of life positing that viewing a union as sacred motivates people to invest effort to protect their bond, especially during times of stress (Mahoney 2013;Mahoney et al 2013;Pargament et al 2017).…”
Section: Discussionsupporting
confidence: 67%
“…Community and national surveys have found that most married Americans view their union as having sacred qualities, such as holy, blessed, sacred (i.e., non-theistic sanctification), and as being a manifestation of a Higher Power (i.e., theistic sanctification) to some degree (e.g., Ellison et al 2011;Mahoney et al 1999). Greater belief regarding sanctity of one's marriage has been tied to greater subjective marital satisfaction, forgiveness, supportive dyadic coping, and sacrifice (e.g., Ellison et al 2011;Rusu et al 2015;Sabey et al 2014). Studies using structural equation or fixed effects modeling with longitudinal data also show that greater sanctification of marriage predicts better observed problem-solving behavior and more positivity by husbands and wives during videotaped interactions where couples were asked to discuss their core conflicts during the TtP (Kusner et al 2014;Rauer and Volling 2015).…”
Section: Sanctification Of Marriagementioning
confidence: 99%
“…Studies suggest that individuals who provide emotion- and problem-focused support to a stressed partner are also more likely to use positive individual coping strategies (e.g., Randall et al, 2015) and report increased well-being (Rusu et al, 2015). In terms of couple benefits, supportive DC is linked to relationship satisfaction in Latino (Falconier et al, 2013b), European (e.g., Ledermann et al, 2010), American (Randall et al, 2015), and Canadian couples (Levesque et al, 2014a) and in Japanese husbands (Yokotani and Kurosawa, 2015).…”
Section: Individual Positive Dc: Supportive DC (Stm-dccm)mentioning
confidence: 99%
“…A considerable amount of studies investigating dyadic coping and relationship outcomes have been published in the past two decades. Dyadic coping has been linked to higher levels of relationship satisfaction [4], relationship stability [10], and partners individual well-being [3,5,11] better psychological adjustment to chronic stress (e.g., medical illness) [12,13] and PLOS ONE better physiological stress responses, such as cortisol recovery and increased immune reactivity [14][15][16].…”
Section: Dyadic Coping and Relationship Satisfaction: Between-and Witmentioning
confidence: 99%
“…Dyadic coping refers to the stress management process in the context of romantic relationships [1,2] and has repeatedly been found to be linked with relationship functioning and individual psychological and physical well-being of the partners [3][4][5]. Several forms of dyadic coping can be distinguished, and the results of a meta-analysis suggest that they differ regarding their importance for relationship satisfaction with supportive dyadic coping (supportive reactions on the other partner's stress signals) and common dyadic coping (joint efforts of a couple to cope with adversities) being the most important dimensions [4].…”
Section: Introductionmentioning
confidence: 99%